Summary of thermal analyses to determine the refrigeration power for the JT-60SA helium refrigerator. (April 2019) - Kamiya, Koji; Natsume, Kyohei; Fukui, Kazuma; Murakami, Haruyuki; Kizu, Kaname; Isono, Takaaki; Wanner, Manfred
Highlights: Procedures to estimate heat loads to JT-60SA cryogenic users are shown. Monte Carlo method is applied to find reasonable heat load contingency. By using exergy calculation, heat loads are converted to 5.64 kW at 4.5 K. Adding pressure drops to heat loads amounts to 7.84 kW at the ACB. The total exergy for cooling of the JT-60SA components is 9 kW at 4.5 K. Abstract: JT-60SA is an upgrade of JT-60U using exclusively superconducting coils to confine the plasma with a typical flat top duration up to 100 s in purely inductive mode. In order to define the helium refrigerator requirements for the superconducting coil system, their thermal protection and the cryopumps, heat loads at different temperature levels have been defined. Because of plasma pulse operation, transient heat pulses appear at the 4 K level for the superconducting coils and the cold structures as well as at the divertor cryopumps of JT-60SA. Since the heat loads were calculated at an earlier stage of the project, the loads of each component design had a certain amount of uncertainty. In JT-60SA, an attempt was made to define reasonable contingencies for the heat load by applying Monte Carlo simulation and put the 99% confidence value of the heat load as requirement for the refrigerator. Exergy analysis of heat loads at different temperatures and the helium mass flows of the JT-60SA resulted in an equivalent refrigeration power of about 9 kW at 4.5 K. This paper summarizes all the thermal analyses performed to determine the refrigeration power of the JT-60SA helium refrigerator.